2005
DOI: 10.26749/rstpp.139.33
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to a catalogue of alien plants in Tasmania

Abstract: The status of 11 alien plant taxa recorded in Tasmania is discussed. Hypericurn hurnifasurn L. and Solanurn arnericanurn Mill. have been recorded only once and further evidence is required to determine their status in Tasmania. Setaria purnila (Poir.) Roem. & Schult. subsp. purnila is a recent incursion of an Australian mainland weed that has been recorded once in Tasmania and has since been eradicated from the recorded site. A treatment of naturalised Cotoneaster Medik. in Tasmania is included. Genista linifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In 22 studies only a few (1-10) individuals were recorded, 39 studies mention 10-100 individuals, in 13 studies the number of individuals varied between 100 and 1000, while 65 studies reported the presence of more than 1000 individuals. Our literature review further revealed the roadside occurrence of P. coronopus in Kuwait (Asia) (Daoud 1975) and in Tasmania (Australia) (Baker 2005). From Hungary 77 occurrences of P. coronopus were reported in the surveyed literature.…”
Section: Literature Reviewmentioning
confidence: 67%
“…In 22 studies only a few (1-10) individuals were recorded, 39 studies mention 10-100 individuals, in 13 studies the number of individuals varied between 100 and 1000, while 65 studies reported the presence of more than 1000 individuals. Our literature review further revealed the roadside occurrence of P. coronopus in Kuwait (Asia) (Daoud 1975) and in Tasmania (Australia) (Baker 2005). From Hungary 77 occurrences of P. coronopus were reported in the surveyed literature.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Geographical origins of plants treated have been determined from various published sources. Definitions of "alien" and "naturalised" and "sparingly naturalised" are in accordance with Baker (2005).…”
Section: Methodsmentioning
confidence: 72%
“…This paper is the fourth of a series (Baker 2005(Baker , 2007(Baker , 2011) which aims to ensure that taxa that become naturalised in Tasmania are formally recorded; that taxa that are present in Tasmania, but have not become fully naturalised ("sparingly naturalised" in the sense of Buchanan (2005) and Baker (2005)) are likewise recorded; that new incursions of alien taxa are recorded; and to maintain up-to-date names for taxa that have been affected by nomenclatural change. In this paper, four species that were introduced as garden ornamentals (Mirabilis jalapa L., Phytolacca octandra L., Coleonema pulchellum I.Williams and Gomphocarpus fruticosus (L.) W.T.Aiton) are treated, giving diagnostic descriptions and notes on their distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical origins of plants treated have been determined from various published sources. Defi nitions of "alien" and "naturalised" and "sparingly naturalised" have been discussed by Baker (2005).…”
Section: Materials and Methods Smentioning
confidence: 99%
“…Management of Tasmania's alien fl ora requires an accurate and up-to-date account of taxa present. 11-iis paper is the third of a series (Baker 2005(Baker , 2007 which aims to ensure that taxa that become naturalised in Tasmania are formally recorded; that taxa that are present in Tasmania, but have not become fully naturalised ["sparingly naturalized" in the sense of Buchanan (2005) and Baker (2005)] are likewise recorded; that new incursions of alien taxa are recorded; and to maintain up-to-date names for taxa that have been affected by nomenclatural change. In this paper, six taxa are treated, giving diagnostic descriptions and notes on their distribution.…”
Section: Introductionmentioning
confidence: 99%